IMPLEMENTASI KESESUAIAN PENYAJIAN LAPORAN KEUANGAN BERDASARKAN SAK ETAP DI KOPERASI CIPTA SEJAHTERA TAHUN 2023 - Fernando, David; Medinal; Maharani, Yunita (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
Implementation of discrepancies presentation of financial reports based on the research facility at prosperous cooperation in 2023. Under the management guidance of the i was given by Mr. Medinal and the second counselor is Ms. Yunita Maharani. The cooperative’s financial report may be said to be based on a sheet, accounting for effort/profit, equity change statements, cash flow statements, and record of financial statement. The study aims to know and analyze how the checkmate applies to creating financial report on prosperous cooperatives. The study is qualitative reseacrh with a descriptive approach aimed at illustrating circumstances based on visible facts using interview techniques, documentation and library studies. Reseacrh award shows up to this day the trademark welfare cooperative financial report is still up to the balance, profit counting reports, equity change statements, cash dlow statements. In addition, the financial statements presented are not yet consistent with the historical case.